By-product Utilization of Industrially Underutilized Cocoa Mucilage through Wine Fermentation - , Hyderali Shihabudheen U. H.; , Prince M. V.; , Sreelakshmi P.; , Sreeja R.; , Lilia Baby; , Rajesh G. K. (Archives of Current Research International, 2025)
Cocoa (Theobroma cacao L.), native to the Amazon basin, was introduced to India in the early 20th century and is now classified as a plantation crop, like coffee, tea, and rubber. Its beans are widely used in chocolates, beverages, and confectionery products. As a plantation crop, proper processing and preservation are essential to ensure product availability. Cocoa pulp is the sweet, white, nutrient-rich mucilage surrounding the beans inside the pod. It contains sugars (glucose, fructose, sucrose), organic acids (mainly citric acid), vitamins (notably ascorbic acid), and minerals such as potassium. Though vital for natural fermentation during cocoa processing, this pulp is often discarded as waste. However, when collected hygienically, it can be used to produce value-added health beverages, like low-alcohol, nutrient-rich wine, offering farmers better resource utilization and income. This study focused on the basic physicochemical properties of cocoa mucilage and wine during fermentation. Parameters such as total soluble solids (TSS), pH, acidity, antioxidant activity (DPPH), total phenolic content (TPC), ascorbic acid, reducing sugars, and color were analyzed. These properties help in understanding the biochemical changes occurring during wine fermentation. The physicochemical properties of cocoa mucilage wine like Total Phenolic Content (TPC), Total Soluble Solids (TSS), Reducing sugar and DPPH scavenging activity tends to increase compared to that of cocoa mucilage. The values of TPC are 107.03 mgGAE/ml and 258 mgGAE/ml for mucilage and wine respectively as well as that of DPPH scavenging activity are 34.3% and 41.72% for mucilage and wine respectively. Whereas pH, acidity and ascorbic acid showed a decreasing trend for wine compared to that of its mucilage. The result of pH is 3.97 and 3.66 for mucilage and wine respectively. These properties highlight its significant potential as a nutrient rich health drink from industrially underutilized cocoa mucilage. Therefore, it can be concluded that cocoa bean mucilage can be used for alcoholic beverage fermentation, contributing to diversifying processing products and increasing the application potentials for cocoa.